A PROSPECTIVE STUDY ON UNUSUAL UTERINE HAEMORRHAGE IN CONJUNCTION WITH CAESAREAN SCAR DEFECT: A PROSPECTIVE COHORT STUDY. - Rajluxmi Tubid (Student's Journal of Health Research, 2023)
Introduction:  A long-term Cesarean section (CS) issue that is gaining increased attention globally is called niche. Not all individuals whose surgical scar from a C-section has a niche have clinical symptoms. The purpose was to evaluate uterine niche predominance in women who experienced abnormal uterine bleeding following C-section. Method:  For one year, nonpregnant women of reproductive age who underwent an abnormal uterine bleeding diagnosis at the gynecology clinic and had a C-section performed more than six months prior were included in the study. The conventional scar measures, residual myometrial thickness, and the width and depth related to the hypoechoic niche were measured by transvaginal ultrasound. Results:  By TVS, the C-section niche was found in 23% of females. Among women with identified niches, premenstrual syndrome was the most common prevalent clinical bleeding tendency. Conclusion:  The CS niche and unexplained abnormal uterine bleeding, particularly postmenstrual spotting, may be related. Recommendation:  Regarding suggestions for averting scar abnormalities from cesarean sections, more randomized controlled trials to be carried out to assess diverse surgical methods. Currently, there is no solid proof that a single technique of one hysterotomy closure is better than the other to avoid scarring from cesarean sections.